Study on Pounding Response of Adjacent Inelastic SDOF Structures Based on Dimensional Analysis - Xuyong Chen; Huipeng Guo; Tao Wang; Qiaoyun Wu (Advances in Civil Engineering)
The dimensional analysis method is applied to study the pounding response of two inelastic single-degree-of-freedom (SDOF) structures under simplified earthquake excitation. The improved Kelvin pounding model is used to simulate the force and deformation of the collider during the contact process. Using bilinear interstory resistance model to simulate the inelastic characteristics of SDOF structures, the expression of dimensionless pounding force and the dimensionless equation of motion during the pounding process are deduced. When dimensionless parameters are used to represent the colliding equation of adjacent inelastic SDOF structures, the variables affecting the pounding response of the adjacent structures are reduced from 14 to 11, which can clearly reflect the rules during the pounding process. The correctness and superiority of the improved Kelvin model are verified by comparing the pounding responses between the improved Kelvin model and Kelvin model. The pounding response of the two inelastic SDOF structures with improved Kelvin model is illustrated in the form of spectra, and the self-similarity of pounding response of the two inelastic SDOF structures is revealed. The effects of structural parameters on the pounding response are analyzed. The results show that the effects of mass ratio, frequency ratio, and initial spacing between the adjacent inelastic SDOF structures on the pounding response of the left-side structure (with smaller mass and stiffness) are closely related to the division of spectral regions. For the right-side structure with larger mass and stiffness, the amplification of pounding on structural response increases with the increase of mass ratio Πm and decreases with the increase of frequency ratio μ and structural spacing Πd.